A correlation between music preferences and personality among undergraduate music students in UiTM Shah Alam / Ahmad Zakri Tomirin - Tomirin, Ahmad Zakri (Faculty of Music, 2014)
This study is actually to investigate a correlation between music preferences and personality among undergraduate music students in UiTM Shah Alam. It identified the correlation between music preferences and personality. Besides that, this study also helps the students of composition department to get an idea of composing their new piece or song. Hence, this study can also help the students to listen a wide range variety of music among music students in UiTM Shah Alam, including Bachelor Degree in Music Performance, Bachelor Degree in Music Composition, Bachelor Degree in Music Education, Bachelor Degree in Music Business and also Diploma in Music.